EVALUASI SISTEM INFORMASI AKUNTANSI PENGUPAHAN PRODUKSI DALAM UPAYA EFEKTIVITAS PENGENDALIAN INTERNAL PT.TM - Sari, Vera Margareta Tunjung; Isharijadi, Isharijadi; Yusdita, Elana Era (Widya Mandala Surabaya Catholic University, 2020)
This study is to evaluate the production wage accounting information system and the effectiveness of internal controls at PT. TM. The approach of this research is descriptive qualitative. This research was conducted at PT. TM in the period of 2019. The results show that the production wage accounting information system at PT. TM is in accordance with the procedures in the company but there is no flowchart. Internal control system for production wages at PT. TM has not been running effectively because there are still weaknesses such as still found multiple function in some parts and a lack of supervision of hired workers.